Histomorphometric and immunohistochemical changes in interstitial cells and ovarian follicles of rats with polycystic ovaries treated with clomiphene citrate. (3rd June 2021) - Lombardi, Leonardo Augusto; Mattos, Leandro Sabará; Simões, Ricardo Santos; Florencio-Silva, Rinaldo; Simões, Manuel de Jesus; Franco, Paulo Celso; Carbonell, Adriana Aparecida Ferraz; Sasso, Gisela Rodrigues da Silva; Baracat, Edmund Chada; Soares-Jr, José Maria
Abstract: Objective: To evaluate the histomorphometric and immunohistochemical changes in interstitial cells and ovarian follicles of rats treated with clomiphene citrate during and after induction of permanent estrus. Methods: Twenty four adult-female rats with regular estrous cycle were equally divided into three groups: (1) GCtrl–at estrous phase. (2) GPCOS–at permanent-estrous phase. (3) GCC–PCOS rats, which remained exposed to 60 days of continuous illumination and treated with Clomiphene Citrate. After that, the animals were euthanized, and the ovaries were removed and processed for paraffin embedding. Sections were stained with H.E. for histomorphometry or subjected to immunohistochemistry for Ki-67 and cleaved caspase-3 detections. Results: The GPCOS showed lack of corpus luteum and several ovarian cysts, as well as interstitial-like cells. The presence of corpus luteum and a significant increase in primary and antral follicles were observed in GCC, which also showed a decrease in the number of ovarian cysts and in the area occupied by interstitial-like cells, as well as a decrease in nuclear volume of interstitial cells. The percentage of cell proliferation was significantly higher in granulosa cells of the GCC. On the other hand, the percentage of apoptosis was significantly higher in the granulosa cells of GPCOS than the GCC. Conclusion: The ovaries of rats treated with clomiphene citrate showed a decrease in the number of cysts, an increase in the number of ovarian follicles, the presence of corpus luteum along with a decrease in the nuclear volume in the area occupied by interstitial cells.